O EFEITO DE BESOUROS ROLA-BOSTA NOS ATRIBUTOS FÍSICOS DO SOLO EM PASTAGEM TROPICAL. - CENTOMA, Gabriel Oliveira; PANACHUKI, Elói; MENEZES, Roniedison da Silva; DOS SANTOS, Wesley Vieira; SANTANA, Carla fernandes; NUNES, Lethicia Fernandes (ANAIS DO ENIC, 2025)
-